Eye movements in reading: Some theoretical context. Issue 3 (March 2013) - Radach, Ralph; Kennedy, Alan
The study of eye movements has proven to be one of the most successful approaches in research on reading. In this overview, it is argued that a major reason for this success is that eye movement measurement is not just a methodology—the control of eye movements is actually part and parcel of the dynamics of information processing within the task of reading itself. Some major developments over the last decade are discussed with a focus on the issue of spatially distributed word processing and its relation to the development of reading models. The survey ends with a description of two newly emerging trends in the field: the study of continuous reading in non-Roman writing systems and the broadening of the scope of research to encompass individual differences and developmental issues.